Elevated jugular venous oxygen saturation after cardiac arrest. (December 2021) - Richter, Jaromir; Sklienka, Peter; Chatterjee, Nilay; Maca, Jan; Zahorec, Roman; Burda, Michal
Abstract: Background: We performed a retrospective analysis of our earlier study on cerebral oxygenation monitoring by jugular venous oximetry (SjvO2 ) in patients of out-of-hospital cardiac arrest (OHCA). The study was focused on high SjvO2 values (≥75%) and their association with neurological outcomes and serum neuron-specific enolase (NSE) concentration. Method: Forty OHCA patients were divided into (i) high (Group I), (ii) normal (Group II), and (iii) low (Group III) SjvO2, with the mean SjvO2  ≥ 75%, 55–74% and <55% respectively. The neurological outcome was evaluated using the Cerebral Performance Category scale (CPC) on the 90th day after cardiac arrest (post-CA). NSE concentration was determined after ICU admission and then at 24, 48, and 72 hours (h) post-CA. Results: High mean SjvO2 occurred in 67% of patients, while no patients had low mean SjvO2 . The unfavourable outcome was significantly more common in Group I than Group II (74% versus 23%, p < 0.01). Group I patients had significantly higher median NSE than Group II at 48 and 72 h post-CA. A positive correlation was found between SjvO2 and PaCO2 . Each 1 kPa increase in CO2 led to an increase of SjvO2 by 2.2 %+/-0.66 (p < 0.01) in group I and by 5.7%+/-1.36 (p < 0.0001) in group II. There was no correlation between SjvO2 and MAP or SjvO2 and PaO2 . Conclusion: High mean SjvO2 are often associated with unfavourable outcomes and high NSE at 48 and 72 hours post-CA. Not only low but also high SjvO2 values may require therapeutic intervention.